Roll-call Votes in the European Parliament - Ondřej Mocek; Markéta Pitrová (Czech Journal of International Relations, 2014)
The text analyses the conditions for the use of the roll-call votes (RCV) in the European Parliament in the context of the democratic accountability to the voters. The research is focused on examining the rules of procedure of this institution from its beginning to the present. The goal of the text is to analyse the formal setting of the rules of RCV. The procedures concerning RCV have been completely in the hands of deputies. The historical analysis therefore endeavours to reveal whether the deputies decided to act in a way that would grant the greatest possible level of transparency and thus control to their voters, or whether the step taken in 2009 is only a historical exception. In the conclusion, the authors come to the result that the MEPs did not strengthen the relations between the voters and the MEPs significantly, although in 2009 and 2014, certain changes were made in this respect.